If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7(x=53)-74=6x+32
We move all terms to the left:
7(x-(53)-74)=0
We add all the numbers together, and all the variables
7(x-127)=0
We multiply parentheses
7x-889=0
We move all terms containing x to the left, all other terms to the right
7x=889
x=889/7
x=127
| 16/c=9 | | 180-x+70+40=180 | | 3t^2-10t-15=0 | | 49=2+r | | 2x+B=150 | | x/20=1200 | | –50p2–18=0 | | 5-7=4-4(x+4)-x | | 3+7=4-(x+5) | | 3-(-8)=7x-5x+5 | | 6x-3x+9=3 | | 7(6+5k)=-27 | | 6x-3x+4=1 | | -19=45m=17 | | 52=4(3x+4) | | 15x4/5+6x-8=180 | | 7x+31=-11 | | 3y+³/y×3=27 | | 110-2x=3(x-10) | | 93=6x-3 | | 6x+6+4x+8+3x+9=2x+10 | | 5/8v=15 | | -5=7x-26 | | 6x-37=-19 | | 69=3x-12 | | 11b+9b=20 | | 14=7x+21 | | (x=10)+(3-5)+x=180 | | k−17=2 | | 5y+35=6(17)+3 | | 19=-5h+4h | | c+15=17 |